THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Marta Muliani; Muhammad Asdar; Abdul Haris (Jurnal Manajemen Dan Bisnis, 2023)
The purpose of this study is to describe and identify or review the literature using several academic journals taken from Google Scholar. This study is based on a systematic literature search to understand how the work environment affects employee performance. There are several limitations in the definition of the journals examined in this study, namely writing obtained through Google Scholar using research-related keywords, namely performance and work environment. This research is based on a national journal which discusses the relationship between the work environment and employee performance in a company or organization that publishes journal articles, articles from 2017 to 2023. The results of the study show that the work environment where the results have a significant impact on employee performance.